2020
DOI: 10.1111/gfs.12489
|View full text |Cite
|
Sign up to set email alerts
|

Impact of increasing shade levels on the dry‐matter yield and botanical composition of multispecies forage stands

Abstract: Botanical diversity has been linked to increased biomass production of grasslands, but these relationships have not been explored as extensively in silvopasture systems where shade impacts on forage mass are variable due to the unique structure and environment of each system. The objective of this study was to evaluate the impact of multiple artificial shade levels on the DM yield and botanical composition of three cool‐season forage mixtures near Blackstone, Virginia, USA. Mixtures were as follows: simple = t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Also forages show adaptation mechanisms to RSR, which resulted in no effect on dry matter yield at 30% RSR (Mercier et al 2020) and 45% RSR or, depending on the crop species, even a slight increase of dry matter yield at 45% RSR . showed that alfalfa, a forage legume, can maintain an adequate photosynthetic activity even under dense shading conditions, suggesting that the light saturation point is reached, which is in general ranging between 25-60% of maximum sunlight for C3 plants ).…”
Section: What Enables the Shade Tolerance Of Some Crop Types?mentioning
confidence: 99%
“…Also forages show adaptation mechanisms to RSR, which resulted in no effect on dry matter yield at 30% RSR (Mercier et al 2020) and 45% RSR or, depending on the crop species, even a slight increase of dry matter yield at 45% RSR . showed that alfalfa, a forage legume, can maintain an adequate photosynthetic activity even under dense shading conditions, suggesting that the light saturation point is reached, which is in general ranging between 25-60% of maximum sunlight for C3 plants ).…”
Section: What Enables the Shade Tolerance Of Some Crop Types?mentioning
confidence: 99%
“…This corresponded with reduced levels of PAR in that system but may also reflect changes in forage species that have been observed under BSP at this site [5,15,16,35]. Changes in forage biomass in response to increasing shade levels are not linear [36] but yield generally declines substantially when PAR is reduced to less than 50% of full sun. Similar yield reductions have been observed in pine-walnut silvopastures in Missouri when compared with OP systems [23].…”
Section: Forage Measures 421 Forage Biomassmentioning
confidence: 59%
“…The experimental systems (OP, BSP, and HSP) were replicated three times and arranged in a randomized complete block design. Thirty-six (36) open Katahdin ewes from Virginia Tech's Southwest Virginia Agricultural Research and Extension Center, Glade Spring, VA were used for the study each year. In 2020, ewes used for the study were 3 to 6 years old with a mean initial body weight of 53 kg ± 0.9 kg.…”
Section: Experimental Design Sheep and Grazing Managementmentioning
confidence: 99%
“…Despite exhibiting higher TS in full sunlight, FA showed lower TS and reduced tiller appearance during summer when cultivated under tree canopies, when compared to DG. As a shade-tolerant specie, DG exhibits the adaptive capacity to modulate its photosynthetic processes, ensuring optimal functionality under low-light conditions (Mercier et al 2020). This inherent trait underscores the species' pro ciency for sustained survival over an extended period within the canopy's shaded environment.…”
Section: Discussionmentioning
confidence: 99%
“…Some C3 species, which can tolerate moderate shade, maintain their productivity as they possess physiological characteristics that allow them to sustain high photosynthetic rates under shaded conditions (Sage and McKown 2006). Dactylis glomerata (orchardgrass; DG) and Festuca arudinacea (tall fescue; FA) are two of the main perennial species cultivated in agroforestry systems (Peri et al 2002;Mercier et al 2020), with DG reported to be more shade tolerant than FA (Peri et al 2002;Mercier et al 2020;Belesky et al 2011). Studies in New Zealand and Uruguay have also demonstrated the positive responses of the biannual grass Holcus lanatus (Yorkshire fog, HL) to shading (Devkota et al 2009;Olmos et al 2011), a specie largely present in oodplain wetlands, with relatively low persistence in dry conditions (Boigné et al 2017).…”
Section: Introductionmentioning
confidence: 99%